Tingkat Kepuasan Konsumen terhadap Produk Olahan Perikanan Amplang UD. XYZ di Samarinda Consumer Satisfaction level on Processed Fishery Products (Amplang) at UD. XYZ in Samarinda City - Hairunnisa; Heru Susilo; Oon Darmansyah (Jurnal Pembangunan Perikanan dan Agribisnis, 2023)
The purposes of the study were determine the characteristics of consumers, consumer satisfaction, and attribute that required to be improved. The research was conducted during 11 months from April 2021 to February 2022 in Samarinda City. The sampling method used purposive sampling to 45 respondents. The data analysis method included descriptive analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The result showed that the characteristics of consumers range around 21-27 years old, most of whom were women with unmarried marital status and status as students with high school graduate with income under Rp. 500,000 every month. The result of the CSI analysis showed a satisfaction level at 79.99% with the criteria of satisfied consumers, while the result of the IPA analysis showed priority of attribute that need to be improved were the nutritional facts.